Causes of Failure of Movie Theatre Industry in Janakpurdham - Sah, Rajesh Kumar; Karn, Binod Lal (Darul Yasin Al Sys, 2024)
Information technology created revolution in the utilization of internet technology. People have been persuading to use internet by replacing newspaper and television. Nowadays, mobile, laptop and other types of gadget are used to watch film. It has been creating challenges day by day to the movie theatre industry. This study aimed to help in formulation of policy at different period for survival of the movie theatre industry in the gradual snowballing phase of internet technology. This research highlighted the causes of decline in watching the film in movie theatre. The public attraction towards movie theatres down falling day by day in Janakpurdham due to cheaper availability of internet as well as flexibility to watch movie at home. These conditions have been forcing the movie theatre industry towards failure in Janakpurdham.